The Effect of Product Innovation and Service Quality on Customer Satisfaction at Jajanan Lembur Shop - Hilma Jakiyah; Asep Zulkifli Achmad (Escalate : Economics and Business Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector face increasingly fierce competition, requiring business actors to continuously innovate products and improve service quality to maintain customer satisfaction. Kedai Jajanan Lembur, one of the culinary MSMEs in Sukaresmi Village, Garut Regency, experiences fluctuations in the number of customer visits, which is suspected to be influenced by product innovation and suboptimal service quality. This study aims to analyze the effect of product innovation and service quality on customer satisfaction, both partially and simultaneously. The research method used is a quantitative method with a descriptive and verification approach. Data were collected by distributing questionnaires to 100 Kedai Jajanan Lembur customer respondents selected using accidental sampling techniques. Data analysis was carried out using classical assumption tests, multiple linear regression analysis, and hypothesis testing using t-tests and F-tests. The results of the study indicate that product innovation and service quality have a positive and significant effect on customer satisfaction, both partially and simultaneously. In conclusion, increasing creative and trend-relevant product innovations and fast, friendly, and professional service quality can significantly increase Kedai Jajanan Lembur customer satisfaction. It is hoped that these findings can be used as consideration for MSMEs in formulating strategies to increase customer satisfaction.